Pembuatan Gaun Pesta Malam Menggunakan Teknik Pola Draping dan Pola Konstruksi - Ariyana Damayanti; Nimas Oktaviani Putri (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Making evening party dresses that must be considered is the pattern. Patterns are used as examples to avoid mistakes when cutting fabric. Pattern making must be adjusted to the size of the body shape of the clothing model. Patterns are very influential on the results of the clothes that will be made, therefore this study uses two different types of pattern techniques, namely draping pattern techniques and construction pattern techniques. This study aims to determine which pattern technique is good for making evening party dresses. This research uses the R&D (research and development) method or can be called research and development. The trial results show that using the draping pattern is more efficient than the construction pattern technique. The practical construction pattern technique has a weakness at the waist, namely the location of the waist that rises from the original waist. After making an assessment through the validator, the author makes evening party dresses using the pattern technique that has the highest value. The making of evening party dresses uses two pattern techniques, namely on the body pattern using a draping pattern technique and on the skirt using a construction pattern technique.